(untitled) (Lundiana: International Journal of Biodiversity, 2007)
The objective of this study was to characterize the galls of Clusia nemorosa G. Mey (Clusiaceae). We selected 30 young plants in trails of Refugio Charles Darwin, an Atlantic forest fragment in Pernambuco, Brazil. The height of each plant was measured and the number of leaves, leaves with galls, and galls per leaf were counted. Leaves with galls were collected from ten specimens and brought to laboratory to be described and to have the inductor observed. We observed galls in only ten individuals of the thirty initially selected. The number of galls per plant varied from 3 to 336. Out of 1,399 leaves inspected, 541 galls were counted in 137 leaves. The galls were deep green, elliptical, crossing the abaxial and adaxial leaf surfaces, preferentially located at the center of the leaf (H=23,48; p<0.01; n=137), but with 49% at the leaf margin. The galls had 5.5 mm and 4.7 mm bearing one larval chamber with one larvae, and were induced by an unidentified species of Hymenoptera.